Case Carburizing Behaviour of Sintered Phosphorus-Containing Ternary Ferrous Powder Compacts - Mohammed Misbahul, Amin; A. U., Malik; Md. Hamiuddin (Z.H. College of Engineering and Technology, Aligarh Muslim University, India, 2009)
The carburizing response of sintered compacts of iron containing phosphorus (0.6%), nickel or molybdenum (2% to 4%) and copper (2% to 4%) has been studied. Hardness variation from case to core was measured for sintered and carburized compacts and microstructures were investigated. It was observed that Fe--0.6P--2Ni--2Cu compact gives a well defined case. Increasing the copper and/or nickel content 4% decreases the sharpness of the case. However, surface hardness increases with increasing nickel content. Similarly, Fe--0.6P--2Mo--2Cu sintered compact gives a relatively better defined case as compared to higher molybdenum or copper containing compacts. Case and core hardness, in general, increase with increasing molybdenum and/or copper content. The results have been discussed on the basis of nature, volume and distribution of pores and specific effects of alloying elements.